2013
DOI: 10.1179/2045772313y.0000000171
|View full text |Cite
|
Sign up to set email alerts
|

Management of bladder dysfunction and satisfaction of life after spinal cord injury in Norway

Abstract: Background: There is limited knowledge about bladder dysfunction and bladder management in persons with spinal cord injury (SCI) after discharge from the hospital in Norway. The impact of bladder dysfunction on satisfaction of life has been rarely explored. Setting: Community-based survey from Norway. Methods: An anonymous cross-sectional postal survey. A questionnaire was sent to the registered members of the Norwegian Spinal Cord Injuries Association. A total of 400 participants, with traumatic or non-trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…We found that the distribution of intermittent (54%), urethral (21%), and suprapubic catheterization (25%) at our institution is similar to recent studies of American patients, but differs from international studies which generally show lower rates of indwelling catheter use . For example, when considering only patients using indwelling or intermittent catheters, the proportion of patients utilizing intermittent catheter is 86‐95% in three Turkish studies, 84% in a Norwegian study, and 47‐54% in two British studies . These geographic differences may be a surrogate for the characteristics of each country's SCI population.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We found that the distribution of intermittent (54%), urethral (21%), and suprapubic catheterization (25%) at our institution is similar to recent studies of American patients, but differs from international studies which generally show lower rates of indwelling catheter use . For example, when considering only patients using indwelling or intermittent catheters, the proportion of patients utilizing intermittent catheter is 86‐95% in three Turkish studies, 84% in a Norwegian study, and 47‐54% in two British studies . These geographic differences may be a surrogate for the characteristics of each country's SCI population.…”
Section: Discussionsupporting
confidence: 72%
“…Vaidyanathan et al discussed barriers to implementing intermittent catheterization in SCI in a case report series and described the following barriers: frequency of catheterization, lack of time to catheterize, lack of public toilets suitable to perform catheterization, anatomical barriers (foreskin, false passage, sphincter spasms, positioning), and medical provider recommendations against intermittent catheterization in patients greater than 60 years old . Hagen and Rekand reported that 23% of the 53 patients studied “use other methods to empty [their] bladder other than disposable catheter because it suits [them] best” and an additional 20.6% report “methods other than intermittent catheterization gives [them] flexibility.” Bakke et al reported on aversion and general health questionnaire (GHQ‐28) scores in patients utilizing intermittent catheterization . They reported that the patient's feelings regarding intermittent catheterization were the most important predictor of distress and discomfort as measured by the GHQ‐28 …”
Section: Discussionmentioning
confidence: 99%
“…In general, the reported historic rates of TUC are higher compared with the present results (1.6%). Mainly, moderate rates (4-9%) have been observed in European studies, 2,19,20 whereas in other parts of the world reported TUC rates range from 17 to 41%. 14,15,18 The use of SPC seems to be similar (11-14%) 14,18 or less common (4-9%) 15,19 compared with present data (13%).…”
Section: Discussionmentioning
confidence: 99%
“…6,17 Other authors have observed lower (that is, 15-33%) 2,14,15,18 or higher (that is, 66-78%) IC rates. 19,20 The discrepancies are the result of differences in the study populations, study designs, national health-care systems and follow-up duration between the studies. The reported data concerning the rate of indwelling catheterization are even more diverse.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Spinal cord injury results in profound disability and these patients have various secondary complication attributable to SCI like neurogenic shock, arrhythmias, autonomic dysfunction, pressure ulcers, bowel and bladder dysfunctions, chronic pain, anxiety, recurrent urinary tract infections. [8][9][10][11][12][13][14][15] These patients have an increased risk for the cardiovascular complications due to hampered mobility and impaired autonomic system.…”
Section: Introductionmentioning
confidence: 99%